Evaluation of temperature stability among different types and grades of vaccine storage units: Data from continuous temperature monitoring devices. Issue 14 (23rd March 2020) - Leidner, Andrew J.; Fisun, Helen; Trimble, Sean; Lucas, Paul; Noblit, Cameron; Stevenson, John M.
Highlight: Both refrigerator and freezer compartments of household-grade combination storage units do not perform as well as household-grade stand-alone or purpose-built storage units. Performance estimates support current vaccine storage and handling guidelines to minimize the use of household-grade combination storage units, particularly the freezer compartments. Abstract: Objective: To evaluate the ability of different types of vaccine storage units to maintain appropriate temperatures for the storage of vaccines and to characterize deviations from recommended temperatures. Data sources: Continuous temperature monitoring devices, or digital data loggers, from vaccine providers who participated in a continuous temperature monitoring pilot project. Study design: We computed descriptive statistics on the percentage of runtime with an out-of-range temperature, or excursion, for different storage unit types (freezers and refrigerators) and for different storage unit grades (household-grade combination, household-grade stand alone, and purpose-built or pharmaceutical grade). We developed frequency histograms for the percentage of storage unit runtime outside of the normal range. We plotted the duration and temperature extrema for identified excursions. Analyses were stratified by storage unit type and grade. Results: Household-grade combination units underperformed relative to household-grade stand-alone and purpose-built units. Among refrigerators, household-grade combination units operated in the normal temperature range an average of 98.9% of their observed runtime, which was lower than 99.4% (p value = 0.038) for household-grade stand-alone and 99.9% (p value < 0.001) for purpose-built units. Among freezers, household-grade combination units operated in the normal temperature range an average of 95.0% of their observed runtime, which was lower than 99.3% (p value < 0.001) for household-grade stand-alone units and 99.7% (p value < 0.001) for purpose-built units. Conclusion: These findings, in particular the underperformance of household-grade combination units relative to household-grade stand-alone and purpose-built units, support current CDC recommendations to avoid the use of household-grade combination storage units when possible.